2020
DOI: 10.2147/cmar.s262674
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Admission Serum Magnesium on the Acute Kidney Injury Among Patients with Malignancy</p>

Abstract: This study aimed to explore the relationship between serum magnesium (Mg) levels and incidence of acute kidney injury (AKI) in patients with malignancy. Patients and Methods: Hospitalized patients with malignancy between October 1, 2014 and September 30, 2015 in Zhongshan Hospital were recruited. All relevant data were extracted from the electronic database. Results: All 99,845 patients were enrolled and 16,082 eligible patients were divided into three groups according to admission serum Mg levels in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…It can counteract vasoconstriction by endogenous catecholamines and potentiate the action of endogenous vasodilators 25 . In a study by Shen et al 13 , they found that low serum magnesium was an independent risk factor for AKI in patients with malignancy, while Cheungpasitporn et al . 26 revealed that both admission hypomagnesemia and hypermagnesemia increased the risk for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…It can counteract vasoconstriction by endogenous catecholamines and potentiate the action of endogenous vasodilators 25 . In a study by Shen et al 13 , they found that low serum magnesium was an independent risk factor for AKI in patients with malignancy, while Cheungpasitporn et al . 26 revealed that both admission hypomagnesemia and hypermagnesemia increased the risk for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, low albumin was not an independent risk factor for AKI, which was considered to be related to the insufficient sample size. Shen et al [ 38 ] showed that hypomagnesemia was associated with a higher incidence of AKI in patients with malignant tumors. When serum magnesium was normal (0.67–1.04 mmol/L), the incidence of AKI was the lowest.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have explored the correlation between serum magnesium and the AKI risk in other kinds of patients including critically ill children, acute pancreatitis, cancer, and those undergoing cardiac surgery [ 19 , 20 , 21 , 22 ]. Three of them discovered that hypomagnesemia was independently correlated with the higher risk of AKI while another one found hypermagnesemia but not hypomagnesemia was correlated with the AKI in critically ill children [ 19 , 20 , 21 , 22 ]. Furthermore, one study with a large sample size verified that both hypermagnesemia and hypomagnesemia could increase the AKI risk in general hospitalized patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serum magnesium level would be influenced by several factors such as thyroid hormone, malnutrition, and gastrointestinal absorption. Additionally, previous studies have found that abnormal serum magnesium level was associated with the AKI development in several kinds of patients, including critically ill children, those diagnosed with acute pancreatitis, cancer, or undergoing cardiac surgery [ 19 , 20 , 21 , 22 ]. Despite this, there is still no study exploring the relationship between serum magnesium level and the AKI development in TBI patients.…”
Section: Introductionmentioning
confidence: 99%